Arms control and global security a document guide - Viotti, Paul R. (Praeger Security International, 2010)
The documents included in this volume are all in the public domain and are collected here as a reference or text for use in arms control or security-related courses. Treaties and conventions are presented for the most part in their full text, although we have had to omit some lengthy and detailed appendices and annexes used by those tasked with implementing these agreements. Although preference is given to printing the full text of treaties or conventions that are legally binding on the parties, volume-length constraints lead us to exercise editorial license on other, often politically binding executive agreements between or among governments, reducing their length to essential elements, with omissions marked by ellipses. Readers may find the full text of appendices, annexes, agreements, or other documents not reprinted here in archives maintained by the UN, other international organizations, and individual nations either online or as hard-copy documents of record.